Penerapan Strategi Bingo Review Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Aqidah Akhlak Kelas VII-1 Dan VII-4 MTs Negeri 2 Langkat - Anida, Marhan Hasibuan, Fadilah Aini Siregar (Pusdikra-Publishing.com, 2022)
The background of this research is that based on the identification carried out by the researchers at the research location, namely: The learning that has been carried out so far at MTs Country 2 Langkat specifically the morals doctrine subject does not emphasize learning by providing direct learning experiences through students' psychomotor development. The objectives of this research are: To find out how the implementation of the Bingo Review strategy in improving students' understanding of the morals doctrine subjects in grades VII-1 and VII-4 of MTs Country 2 Langkat. This research is an experimental type of research with a quantitative approach. However, it does not deny that a qualitative approach to research is used to analyze data on the ability of teachers to manage learning and student activities while the bingo review strategy is applied as well as to analyze data about student learning in the morals doctrine subject at MTs Country 2 Langkat. After the data has been collected, the research is analyzed using the method of observation, documentation and testing or tests. Then the research is described to obtain conclusions using the t test data analysis technique. The results of this study are: The results of the study indicate that the bingo review strategy is effective in increasing students' understanding of the morals doctrine subject at MTs Country 2 Langkat. It can be seen based on the results of statistical data analysis with the calculation of the t test with the results of t count: 4,651 > t table: 2.00 then Ho is rejected and Ha is accepted. This means that the application of the Bingo review strategy can improve student learning outcomes in the morals doctrine subject at MTs Country 2 Langkat. This means that the Bingo review strategy can improve student understanding. Then the Bingo review strategy is effectively implemented at MTs Country 2 Langkat